2023
DOI: 10.1021/acs.jafc.2c08390
|View full text |Cite
|
Sign up to set email alerts
|

Odorant-Binding Protein 6 Contributes High Binding Affinity to Insecticides in a Parasitic Wasp Meteorus pulchricornis (Hymenoptera: Braconidae)

Abstract: Meteorus pulchricornis is a preponderant parasitic wasp of various lepidopteran pests. The extensive application of broad-spectrum insecticides usually causes serious threats to the olfactory recognition of nontarget insects such as parasitoid wasps. However, the binding mechanism of odorant-binding proteins (OBPs) to insecticides in parasitoid wasps remains unknown. Herein, we find that the MpulOBP6 protein had a strong binding affinity to three insecticides (phoxim, chlorpyrifos, and chlorfenapyr). Results o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 50 publications
0
15
0
Order By: Relevance
“…29 In addition to plant or insect host volatiles, the interactions between MpulOBP6 of Meteorus pulchricornis and three insecticides were also investigated recently. 36 However, most of these reports focused on OBPs and ORs involved in host location by parasitic wasps, and there is a lack of studies on the olfactory function of NPC 2s. 29,34−36 NPC 2s have been extensively studied in the context of NPC diseases that occur in humans and are related to the mutations or absence of NPC2 genes, 38 and they are also proved to mediate lipid metabolism and immune signaling pathways in some vertebrates.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…29 In addition to plant or insect host volatiles, the interactions between MpulOBP6 of Meteorus pulchricornis and three insecticides were also investigated recently. 36 However, most of these reports focused on OBPs and ORs involved in host location by parasitic wasps, and there is a lack of studies on the olfactory function of NPC 2s. 29,34−36 NPC 2s have been extensively studied in the context of NPC diseases that occur in humans and are related to the mutations or absence of NPC2 genes, 38 and they are also proved to mediate lipid metabolism and immune signaling pathways in some vertebrates.…”
Section: Discussionmentioning
confidence: 99%
“…Parasitic wasps play a critical role in maintaining ecosystem stability, and most parasitic wasps are important natural enemies used for pest control. It would be helpful to improve the applications of parasitoids for biocontrol by clarifying their chemical perception process during mate finding, host location and oviposition. ,, For this reason, the olfactory communication mechanism of parasitic wasps has gradually received increased amounts of attention. , For example, previous studies have shown that AjapOR35 mediates the attractiveness of β-caryophyllene and (E)-α-farnesene to Anastatus japonicusis; CchlOR62 participates in the detection of the female wasps attractant cis -jasmone in Campoletis chlorideae; and CcunOBP2 has strong binding affinity for the parasitoid attractant 3-carene in Chouioia cune . In addition to plant or insect host volatiles, the interactions between MpulOBP6 of Meteorus pulchricornis and three insecticides were also investigated recently . However, most of these reports focused on OBPs and ORs involved in host location by parasitic wasps, and there is a lack of studies on the olfactory function of NPC 2s. , …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has previously been demonstrated that a single OBP may identify and bind numerous odorant chemicals. 7,23,41 We discovered that GmolOBP1 was selectively expressed on antennae and that eight odor molecules caused a strong EAG response with antennae. As a result, we determined that GmolOBP1 was implicated in the recognition of pear volatiles.…”
Section: ■ Associated Contentmentioning
confidence: 99%
“…Other than acute effects on target insect pests, chemical insecticides cause serious negative effects on nontarget insects, such as parasitoid wasps and pollinators ( 162 ). Several studies reported that the OBP either showed high binding affinity to insecticides ( 154 , 158 ) or the binding of OBP to floral volatile was significantly affected by insecticides ( 163 ). These studies implied that OBPs may contribute to olfaction based behavioral response to insecticides.…”
Section: Diverse Roles Of Insect Obps In Communication and Xenobiotic...mentioning
confidence: 99%